Clinical cytological study of patients with ascites in a national general hospital in Peru - Carrasco, Juan (2022)
Objective. To evaluate the sensitivity, specifcity and predictive values of theclinical cytological study of patients with ascites in a national general hospital in Peru. Methods. Patients presenting with clinical manifestations of ascites, biochemical, cytological and histological studies were included. Results. Fifteen patients with ascites were studied. The mean age was 62 years, being 80% female and 20% male. The fnal diagnoses revealed various malignant neoplasms (93.3%) and peritoneal tuberculosis (6.7%). The most frequent clinical manifestation was mild to severe abdominal pain (80%). The cellular components were: red blood cells (73.3%), histiocytes (26.7%), lymphocytes (73.3%), polymorphonuclear cells (40%), mesothelial cells (86.7%) and clusters of epithelioid cells with varying degrees of atypia (80%). Two casesshowed atypical lymphoid cells. The sensitivity and positive predictive valuewere 87% and 80%, respectively. Conclusions. According to a dichotomous test, the present study demonstrates the high sensitivity and high positive predictive value of the clinical cytologic study in patients with ascites